2017
DOI: 10.18632/oncotarget.19534
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 activates the Wnt/β-catenin signaling pathway in colon cancer

Abstract: Purpose and MethodsThe translocation of β-catenin/CTNNB1 to the nucleus activates Wnt signaling and cell proliferation; however, the precise mechanism underlying this phenomenon remains unknown. Previous reports have provided evidence that NOTCH1 is involved in the Wnt signaling pathway. Therefore, we sought to determine the mechanism by which NOTCH1 influences the Wnt/β-catenin pathway. We constructed a vector expressing the NOTCH1 intracellular domain (NICD1) and transfected the vector into HCT116 which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 53 publications
(58 reference statements)
0
23
1
Order By: Relevance
“…Some evidence has indicated that cell fate determination and lineage commitment of enterocytes are not governed by a simple rule, but by a complex and multilayered interaction between several pathways [46]. This means that β-catenin is regulated in many ways, for example, NOTCH1 plays a key role in the Wnt pathway, and activation of NOTCH1 is associated with the translocation of β-catenin to the nucleus in colon cancer [47]. Axin expression is positively regulated by β-catenin, and this generates a negative feedback loop that would be expected to decrease cytosolic β-catenin levels [48].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has indicated that cell fate determination and lineage commitment of enterocytes are not governed by a simple rule, but by a complex and multilayered interaction between several pathways [46]. This means that β-catenin is regulated in many ways, for example, NOTCH1 plays a key role in the Wnt pathway, and activation of NOTCH1 is associated with the translocation of β-catenin to the nucleus in colon cancer [47]. Axin expression is positively regulated by β-catenin, and this generates a negative feedback loop that would be expected to decrease cytosolic β-catenin levels [48].…”
Section: Discussionmentioning
confidence: 99%
“…2B). Notch1 functioned as an important role in the Wnt/β-catenin pathway, and the activation of Notch1 was positively related to the nuclear translocation of β-catenin 22 . The accumulation of β-catenin in the nucleus plays an important role in the malignant progression of tumours.…”
Section: Dner Induces Emt In Bc Cellsmentioning
confidence: 99%
“…These studies highlight the importance of NOTCH pathway activation in the maintenance of colon cancer stem cells and in colon cancerogenesis. Interestingly, NOTCH1 was shown to activate the WNT/β-catenin signaling pathway in colon cancer [ 416 ]. In this context, the analysis of primary colon cancer samples showed that the activation of NOTCH1 is associated with the translocation of β-catenin in the nucleus [ 416 ].…”
Section: Colon Cancer Stem Cellsmentioning
confidence: 99%